Nitrogen Fixation by Trichodesmium and unicellular diazotrophs in the northern South China Sea and the Kuroshio in summer - Chao Wu (Nature Portfolio, 2018)
Abstract Distribution of diazotrophs and their nitrogen fixation activity were investigated in the northern South China Sea (nSCS) and the Kuroshio from July 16th to September 1st, 2009. N2 fixation activities in whole seawater and <10 μm fraction at the surface were measured by acetylene reduction assay. Higher activities were observed at the East China Sea (ECS) Kuroshio and the nSCS shelf. The nSCS basin showed a low N2 fixation activity. The <10 μm fractions (unicellular diazotrophs) contributed major portion to the whole-water activity in the survey time, indicating that nanoplanktonic cyanobacterias were the major diazotrophs in the survey area. Daily N2 fixation rates of Trichodesmium ranged from 0.11 to 9.83 pmolNtrichome−1 d−1 with an average of 4.03 pmolNtrichome−1 d−1. The Luzon Strait and the ECS Kuroshio had higher N2 fixation rates of Trichodesmium than the nSCS shelf and basin. Calculated activities of Trichodesmium at most stations were moderately low compared with that of the whole-water. The contribution of N2 fixation by the whole-water to primary production ranged from 1.7% to 18.5%. The estimated amount of new nitrogen introduced by Trichodesmium contributed up to 0.14% of the total primary production and 0.41% of the new production in the Luzon Strait.